Perlindungan, Pengamanan, dan Penyelamatan Arsip Vital Pengadilan Tinggi Padang - Utami, Riven Raviah; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This research aims to describe (1) identification of activities or selection of vital records in the High Court of Padang, (2) the protection and security of vital records in the High Court of Padang, and (3) rescue and recovery of vital records High Court of Padang. Writing this using qualitative methods, analyzing the data carried by describing and explaining data. Data were collected by interview and observation. Based on data analysis, it can be concluded. (1) High Court idetifikasi Padang vital records have not been performing well, because many vital records are not identified as a result of the vital records that do not match the identification process. (2) the protection and security of vital records in the High Court of Padang done differently in each part. (3) Rescue and recovery of vital records in the High Court has never dilaksnakan Padang, because the archive at the High Court in Padang have never experienced a disaster or calamity.